2015
DOI: 10.3109/10428194.2015.1080364
|View full text |Cite
|
Sign up to set email alerts
|

Cross-platform assessment of genomic imbalance confirms the clinical relevance of genomic complexity and reveals loci with potential pathogenic roles in diffuse large B-cell lymphoma

Abstract: Genomic copy number alterations (CNAs) in diffuse large B-cell lymphoma (DLBCL) have roles in disease pathogenesis but overall clinical relevance remains unclear. Herein, an unbiased algorithm was uniformly applied across three genome profiling datasets comprising 392 newly-diagnosed DLBCL specimens that defined 32 overlapping CNAs, involving 36 minimal common regions (MCRs). Scoring criteria were established for 50 aberrations within the MCRs while considering peak gains/losses. Application of these criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For example, CNOT2 was generally hypomethylated, overexpressed, and observed CNA gains, which is a predicted scenario for a proto-oncogene. CNOT2 was also predicted to be an oncogene based on CNA and expression profiling data from 392 DLBCL patient samples (39). HIVEP2, a predicted TSG in our screen, had a similar level of methylation and CNAs as 3 known TSGs (TP53, CDKN2A, and TNFAIP3), suggesting HIVEP2 is a TSG in human DLBCL.…”
Section: Comparative Genomics Of Ciss In Cancer Including Lymphomamentioning
confidence: 63%
“…For example, CNOT2 was generally hypomethylated, overexpressed, and observed CNA gains, which is a predicted scenario for a proto-oncogene. CNOT2 was also predicted to be an oncogene based on CNA and expression profiling data from 392 DLBCL patient samples (39). HIVEP2, a predicted TSG in our screen, had a similar level of methylation and CNAs as 3 known TSGs (TP53, CDKN2A, and TNFAIP3), suggesting HIVEP2 is a TSG in human DLBCL.…”
Section: Comparative Genomics Of Ciss In Cancer Including Lymphomamentioning
confidence: 63%
“…We demonstrated a clear association between inferior clinical outcome and increased genomic complexity in FL. This was proposed previously in DLBCL, 16,17 although the criteria in calling aberration were different in each study. Monti et al specifically evaluated CNAs in genomic regions encompassing genes of the CDKN2A-TP53-RB-E2F axis and showed that any CNA in these regions predicted inferior OS in DLBCL.…”
Section: Discussionmentioning
confidence: 92%
“…16 Dias et al proposed that CNA in a panel of genomic regions predicts outcome. 17 Given the various criteria used to define "complex" genome, caution must be exercised when applying this parameter as a marker across different platforms and cohorts. We therefore focused on evaluating the prognostic significance of specific chromosome arms and subregions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly treated reference DNA (normal male: female genomic DNA, Promega, Madison, WI, USA) and the tumor DNA were differentially labeled and hybridized to a targeted oligonucleotide array representing genomic regions commonly altered in mature B-cell neoplasms (Agilent Technologies Inc., Santa Clara, CA, USA) as previously described. 12,13 Data were extracted using Feature Extraction Version 10.7.3.1 (Agilent) and sites of gain/loss identified using the Rank segmentation algorithm within the Nexus Copy Number Analysis Software (Version 6.1, Biodiscovery Inc., Hawthorne, CA, USA) where an average log2 ratio change of ± 0.3 was considered acceptable for a minimum of eight consecutive probes. All gains/loss were visually confirmed by examining log ratio profiles and all genomic coordinates are given according to the NCBIbuild37/hg19 assembly.…”
Section: Fluorescence In Situ Hybridization and Array Comparative Genmentioning
confidence: 99%
“…12 Briefly, if the bulk of the DNA was greater than 800 bp in size, heat fragmentation was performed until the bulk DNA was 400-800 bp. Similarly treated reference DNA (normal male: female genomic DNA, Promega, Madison, WI, USA) and the tumor DNA were differentially labeled and hybridized to a targeted oligonucleotide array representing genomic regions commonly altered in mature B-cell neoplasms (Agilent Technologies Inc., Santa Clara, CA, USA) as previously described.…”
Section: Fluorescence In Situ Hybridization and Array Comparative Genmentioning
confidence: 99%